Physiological instability is linked to mortality in primary central nervous system lymphoma: A case–control fMRI study. Issue 13 (11th May 2022) - Poltojainen, Valter; Kemppainen, Janette; Keinänen, Nina; Bode, Michaela; Isokangas, Juha‐Matti; Kuitunen, Hanne; Nikkinen, Juha; Sonkajärvi, Eila; Korhonen, Vesa; Tuovinen, Timo; Järvelä, Matti; Huotari, Niko; et al.
Abstract: Primary central nervous system lymphoma (PCNSL) is an aggressive brain disease where lymphocytes invade along perivascular spaces of arteries and veins. The invasion markedly changes (peri)vascular structures but its effect on physiological brain pulsations has not been previously studied. Using physiological magnetic resonance encephalography (MREGBOLD ) scanning, this study aims to quantify the extent to which (peri)vascular PCNSL involvement alters the stability of physiological brain pulsations mediated by cerebral vasculature. Clinical implications and relevance were explored. In this study, 21 PCNSL patients (median 67y; 38% females) and 30 healthy age‐matched controls (median 63y; 73% females) were scanned for MREGBOLD signal during 2018–2021. Motion effects were removed. Voxel‐by‐voxel Coefficient of Variation (CV) maps of MREGBOLD signal was calculated to examine the stability of physiological brain pulsations. Group‐level differences in CV were examined using nonparametric covariate‐adjusted tests. Subject‐level CV alterations were examined against control population Z‐score maps wherein clusters of increased CV values were detected. Spatial distributions of clusters and findings from routine clinical neuroimaging were compared [contrast‐enhanced, diffusion‐weighted, fluid‐attenuated inversion recovery (FLAIR) data]. Whole‐brain mean CV was linked to short‐term mortality with 100% sensitivity and 100% specificity, as all deceased patients revealed higher values ( n  = 5, median 0.055) than surviving patients ( n  = 16, median 0.028) ( p <  .0001). After adjusting for medication, head motion, and age, patients revealed higher CV values (group median 0.035) than healthy controls (group median 0.024) around arterial territories ( p  ≤ .001). Abnormal clusters (median 1.10 × 10 5 mm 3 ) extended spatially beyond FLAIR lesions (median 0.62 × 10 5 mm 3 ) with differences in volumes ( p =  .0055). Abstract : This is the first study in PCNSL that analyses physiological brain pulsations. Our results suggest that perivascular PCNSL infiltration causes instability of physiological pulsations in otherwise radiologically intact vascular territories. Furthermore, this data suggests that noninvasive CV may be linked to short‐term mortality in PCNSL despite a promising treatment regimen.